Morphophysiological and proteomic profiling unveiling mechanisms underlying nitrogen use efficiency in popcorn (Zea mays var. everta) - de Oliveira Santos, Talles (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.